Effects of upper respiratory tract infections in patients with cystic fibrosis. Issue 11 (November 1996) - Collinson, J; Nicholson, K G; Cancio, E; Ashman, J; Ireland, D C; Hammersley, V; Kent, J; O'Callaghan, C
Abstract : BACKGROUND: The polymerase chain reaction has improved the detection of picornaviruses and rhinoviruses and our understanding of their role in reversible airways disease. The effects of colds on lower respiratory morbidity and bacterial colonisation in cystic fibrosis remain uncertain. METHODS: Children with cystic fibrosis were evaluated regularly in the clinic and the parents notified the investigators when their child developed a cold. Nasopharyngeal specimens were collected at the start of the infection for polymerase chain reaction, bacteriology was also undertaken and again three weeks later, and pulmonary function was measured in children aged > or = 6 years at four day intervals for three weeks. The effects of colds on rate of progression of cystic fibrosis were assessed by pulmonary function, Shwachman scores, and radiology. RESULTS: Thirty eight children suffered 147 colds over 17 months. Picornaviruses were detected in 51 (43%) of 119 nasopharyngeal specimens, and 21 of the 51 were further identified as rhinoviruses. Pulmonary dysfunction was similar following picornavirus and non-picornavirus infections; the mean change from baseline in forced expiratory volume in one second (FEV1) was -16.5% and -10.3% at 1-4 days and 21-24 days, respectively, after onset of a cold. Children who experienced more colds than average had evidence of disease progression with reduction in Shwachman score, increasing Chrispin-Norman score, and greater deterioration in FEV1 per annum. Ten of 12 new bacterial infections were associated with a cold. CONCLUSIONS: Picornavirus and non-picornavirus colds are associated with pulmonary function abnormalities and disease progression in patients with cystic fibrosis, and predispose to secondary bacterial infection and colonisation.